Fiscal measures for employment promotion in developing countries - International Labour Office; International Labour Office (Geneva : International Labour Office, 1972)
This volume is concerned mainly with how fiscal measures can increase employment through influencing product mix and the choice of production techniques.
Includes bibliographical references.
sju 22/01/2019
Loans
Keywords: Full employment policies; Fiscal policy